2020
DOI: 10.3390/ijerph17124363
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Regulatory Approaches to Rehabilitation Planning: A Concise Overview of Current Laws and Policies Addressing Access to Rehabilitation in Five European Countries

Abstract: Background: The rising prevalence of disability due to noncommunicable diseases and the aging process in tandem with under-prioritization and underdevelopment of rehabilitation services remains a significant concern for European public health. Over recent years, health system responses to population health needs, including rehabilitation needs, have been increasingly acknowledging the power of law and formal written policies as strategic governance tools to improve population health outcomes. However, the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Other research has identified disparities in rehabilitation service utilisation for older people based on SES and the need for strategies to address underserved populations with unmet rehabilitation needs (Gell et al., 2017). Rehabilitation programs often use a disease specific model, where rehabilitation programs are siloed by health condition (Garg et al., 2020; Kamenov et al., 2019), excluding people with multimorbidity and frailty (Barker et al., 2018; Carlesso et al., 2020). Focusing on addressing the functional limitations, rather than on disease specific programs, could better address the needs of older people with complex conditions (Beard & Bloom, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other research has identified disparities in rehabilitation service utilisation for older people based on SES and the need for strategies to address underserved populations with unmet rehabilitation needs (Gell et al., 2017). Rehabilitation programs often use a disease specific model, where rehabilitation programs are siloed by health condition (Garg et al., 2020; Kamenov et al., 2019), excluding people with multimorbidity and frailty (Barker et al., 2018; Carlesso et al., 2020). Focusing on addressing the functional limitations, rather than on disease specific programs, could better address the needs of older people with complex conditions (Beard & Bloom, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Key stakeholders acknowledged access to community rehabilitation services for older people was limited. Garg et al (2020) studied health law and policy in Germany, Netherlands, Sweden,…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations